2020
DOI: 10.1007/s11926-020-00911-w
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Musculoskeletal Ultrasound in the Rheumatoid Arthritis Continuum

Abstract: Purpose of Review Rheumatoid arthritis (RA) is no longer considered a fixed phenotype but rather a disease continuum. This review outlines the current and potential value of applying ultrasound (US) along this continuum: from the prediction of progression to RA in at-risk individuals, to confirmation of the early diagnosis of RA, as well as the consideration of differential diagnoses, and the use in disease monitoring and defining remission. Recent Findings In individuals at-risk of RA (i.e., positive autoanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 77 publications
0
22
0
Order By: Relevance
“…Another way to investigate this question in more detail would be to compare the MRI images with a second imaging modality. Ultrasound is potentially useful for this purpose, as it plays an important role in the imaging of RA throughout the whole course of the disease [ 22 ]. MRI provides excellent soft tissue contrast and multiplanar imaging with excellent reproducibility [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another way to investigate this question in more detail would be to compare the MRI images with a second imaging modality. Ultrasound is potentially useful for this purpose, as it plays an important role in the imaging of RA throughout the whole course of the disease [ 22 ]. MRI provides excellent soft tissue contrast and multiplanar imaging with excellent reproducibility [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the European Society of Musculoskeletal Radiology and the European League Against Rheumatism recommendations, MRI is considered the best noninvasive, observer-independent imaging modality for the evaluation of joint and tendon inflammation [ 24 , 25 ]. However, MRI is costly and has limited availability [ 22 ]. Advances in ultrasound transducer technology and improvements in the sensitivity of Doppler imaging have increased the usefulness of ultrasound for RA, particularly as signs of acute inflammation, such as synovial and tenosynovial effusion, are detectable [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…While in RA studies have demonstrated that subclinical inflammation can be found on US in patients which are in clinical remission according to the clinical measures [30] and that US-detected residual synovitis can predict the risk of relapse and structural progression [31,32], in paediatrics this has not been definitely proven. Indeed, despite growing evidence supporting the potential role of US in the monitoring of patients, the use of US is still a matter of debate even in RA.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the early identification of bone erosions may raise important implications for the management (including the therapeutic approach) of SLE patients with 'active' arthritis; in these patients, treatment should be aimed at preventing further joint damage and disability. In RA, bone erosions are important prognostic biomarkers for disease severity; their presence has been associated with poor functional outcome and irreversible loss of function [43][44][45]. In this context, sensitive imaging tools, such as US and MRI, have the potential to provide valuable information regarding the detection of joint damage in SLE patients; the value of these imaging tools is arguably highest in patients with very early inflammatory arthritis, where the sensitivity of CR (the reference imaging tool for the assessment of joint damage in RA) has been proven to be low (Fig.…”
Section: Joint Structural Damagementioning
confidence: 99%